The implemetation of mass customization for cars in Malaysia - 201722 Lee, Yew Jin (Skudai : Universiti Teknologi Malaysia, 2006)
Project Paper (Sarjana Muda Kejuruteraan (Mekanikal - Automotif)) - Universiti Teknologi Malaysia, 2006